Mechanisms and Therapeutic Targets of microRNA-associated Chemoresistance in Epithelial Ovarian Cancer - Zhang, Lingyun; Nadeem, Lubna; Connor, Kristin; Xu, Guoxiong (Current Cancer Drug Targets, 2016)
Epithelial ovarian cancer (EOC) is the most lethal disease among gynecologic malignancies. Despite increasing knowledge of ovarian cancer biology and advances in treatment efficacy, the survival rate of patients with EOC has not improved over the past two decades. Patients with an advanced disease often relapse due to the development of chemoresistance. Recent in vivo and in vitro studies have shown insight into the mechanisms of such drug resistance, including a potential role for microRNAs (miRNA, miR) in the process of chemoresistance. In this review, we provide an overview of current therapeutic targets of miRNA-associated chemoresistance in EOC and discuss potential therapeutic values and molecular mechanisms by which miRNAs influence the development and reversal of chemoresistance.
Keywords: oncogene